The Influence of a Ceramic Recoater Blade on 3D Printing using Direct Metal Laser Sintering - Daňa, Milan; Zetková, Ivana; Hanzl, Pavel (Manufacturing Technology Journal, 2019)
This paper deals with 3D printing of metal parts. There are many principles of 3D printing, for example, DMLS, SLS, CLADDING, etc. This paper is limited to 3D printing using DMLS (Direct Metal Laser Sintering). 3D printing using DMLS can create complex geometries that cannot be created using other metal manufacturing processes. This principle is based on sintering of metal powder in thin layers. Thin layers of powder are applied by a recoater blade. The shape of the part is sintered with a precise and high-wattage laser in this layer. The part is built layer by layer. The printer used for the experimental part of this paper was an EOS M290. The material of the recoater blade was ceramic and the powder material was MS1. There are several types of recoater blade but this article focuses on the limitations of using a ceramic blade recoater. The influence of the orientation and size of support structures depending on the recoater blade was examined. Also, the effect of the height of the support structures on their vibrations was investigated and the vibration of the support structures was described in detail. The influences and limitations of the recoater blade were investigated.
Keywords: 3D print; DMLS; MS1 - 1.2709; recoater blade; limitations